A Single-Dose Intra-Articular Morphine plus Bupivacaine versus Morphine Alone following Knee Arthroscopy: A Systematic Review and Meta-Analysis. - Dong-Xing Xie; Chao Zeng; Yi-Lun Wang; Yu-Sheng Li; Jie Wei; Hui Li; Tuo Yang; Tu-Bao Yang; Guang-Hua Lei (PLoS ONE)
Objectives The purpose of this study was to compare the efficacy and safety of a single-dose intra-articular morphine plus bupivacaine versus morphine alone in patients undergoing arthroscopic knee surgery. Methods Randomized controlled trials comparing a combination of morphine and bupivacaine with morphine alone injected intra-articularly in the management of pain after knee arthrocopic surgery were retrieved (up to August 10, 2014) from MEDLINE, the Cochrane Library and Embase databases. The weighted mean difference (WMD), relative risk (RR) and their corresponding 95% confidence intervals (CIs) were calculated using RevMan statistical software. Results Thirteen randomized controlled trials were included. Statistically significant differences were observed with regard to the VAS values during the immediate period (0-2h) (WMD -1.16; 95% CI -2.01 to -0.31; p = 0.007) and the time to first request for rescue analgesia (WMD = 2.05; 95% CI 0.19 to 3.92; p = 0.03). However, there was no significant difference in the VAS pain score during the early period (2-6h) (WMD -0.36; 95% CI -1.13 to 0.41; p = 0.35), the late period (6-48h) (WMD 0.11; 95% CI -0.40 to 0.63; p = 0.67), and the number of patients requiring supplementary analgesia (RR = 0.78; 95% CI 0.57 to 1.05; p = 0.10). In addition, systematic review showed that intra-articular morphine plus bupivacaine would not increase the incidence of adverse effects compared with morphine alone. Conclusion The present study suggested that the administration of single-dose intra-articular morphine plus bupivacaine provided better pain relief during the immediate period (0-2h), and lengthened the time interval before the first request for analgesic rescue without increasing the short-term side effects when compared with morphine alone. Level of evidence Level I, meta-analysis of Level I studies.